Recent Advancements in Treatment and Prevention of Substance Use Disorders - Sudheesh, S.; Gowda, S. N. Nanjunde (Innovational: Journal of Nursing and Healthcare, 2024)
Substance use disorder (SUD) commonly referred to as addiction. It is a medical illness with altered behavioral, cognitive, physical, neurobiological, and affective functions associated with compulsive and repeated use of addictive substance(s), whether legal or illegal. Research findings over the past two decades have substantially enhanced our knowledge of the neurobiological mechanisms and complexity of the illness caused by SUDs. As presented in the extensive reviews in this collection, we now understand that, unlike many other diseases, pharmacotherapy or behavioral/cognitive therapy alone is unlikely to be enough to either restore the damaged system(s) or to prevent relapse and sustain recovery from addiction. There are advancements in the treatment of SUD which includes the advanced thought in the care of treatment from receiving the patient to discharge the patient. It also includes community and industrial treatment policies and various awareness programs. The health care workers knowledge of treatment is highly helpful to achieve the goal in the care of patient. Creating a toll-free number for affected individuals or their families or friends to approach. Posters/pamphlets/notices to be displayed. Seeking help from the media including print, TV, and radio. Health department to be trained for referral and follow-up. Integrated Rehabilitation and Counselling Centre for Addicts sponsored by Ministry of Social Justice and Empowerment to be made accessible for persons with addiction for availing free services. Private doctors need to be sensitized. Rural camps can be conducted in partnership with appropriate treatment centers and a host organization from the community.